Angklung Buncis Sebagai Sarana Pengembangan Perilaku Cinta Tanah Air - Lusvinaningtyas Lusvinaningtyas; Alfira Putri Febryanis; Neng Riski Ayu Utami; Dede Wahyudin; Jennyta Caturiasari (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The development of patriotism behavior is one part of several important points in character education. In the context of culture, art is an important and inseparable part of human culture. In fact, in a narrow view, it is not uncommon for people to interpret and identify culture as art. Art is one element of culture. Art is a very important part of culture. Art is an expression of creativity from the culture itself. The purpose of this study was to find out and analyze the art of angklung buncis in Cireundeu village as a means of developing patriotism behavior for elementary school students in Cireundeu village. For what factors cause angklung buncis in Cireundeu village to develop love for the country. This study uses qualitative research. The research subjects used in this study were parties who became informants for the research being carried out. The approach used in this study is a qualitative research approach, namely research conducted by collecting data, questions that have been prepared by researchers to solve the focus of the problems set in the research. Data collection techniques using interviews, observation, and documentation studies. The Cireundeu tradition seeks to continue to preserve the art of angklung beans. One way is to introduce and maintain the tradition and invite the younger generation to always protect it by practicing playing the Angklung Buncis for ceremonial purposes or other purposes such as entertainment and performing arts.